Green industries without institutional support: the case of the Danish wine industry - Zorn, Anika; Schäfer, Susann (Tijdschrift voor economische en sociale geografie, 2026)
Green regional industries are increasingly recognised as pivotal in addressing diverse environmental crises. While the role of institutions in fostering green industries is well-established, limited research exists on the dynamics of green industry creation without institutional support. Employing a mixed-method approach, we investigate the case of the Danish wine industry to analyse the relationships and conditions facilitating the greener wine industry of Denmark. Our results reveal that Danish winegrowers successfully establish a new industry with reduced fungicide usage by mobilising environmental innovations from other winegrowing regions without institutional support. Local actors' agency and their ability to create legitimacy and a local market emerge as critical factors shaping this process. This study highlights strategies of local actors and specific conditions that enable local actors to mobilise resources from other regions without institutional support to create a new green industry. The findings provide valuable insights for scholars of economic geography and green transition studies.